The dementias of schizophrenia - Ricardo de Oliveira-Souza; Rogério Paysano Marrocos; Jorge Moll (Dementia & Neuropsychologia)
Abstract Cases of "adolescent insanity" were known to Kraepelin's forerunners and lay at the core of his concept of dementia præcox. In the post-neuroleptic era it became clear that dementia may also occur in schizophrenia as a fully reversible state depending on psychopathological status. In the present review we discuss the validity of applying the concept of dementia to schizophrenia. We concur with the view that schizophrenia may lead to a true dementia both (i) as a fixed end-stage consequence of the disease process itself, or (ii) as a drug-responsive reversible state. There is an urgent need to examine the patterns of dementia in other common neuropsychiatric disorders, employing current methods of neurobehavioral investigation.